Advancements and future prospective of DNA barcodes in the herbal drug industry - Mahima, Karthikeyan; Sunil Kumar, Koppala Narayana; Rakhesh, Kanakarajan Vijayakumari; Rajeswaran, Parameswaran Sathiya; Sharma, Ashutosh; Sathishkumar, Ramalingam (Frontiers in Pharmacology, 2022)
Ethnopharmacological relevance: The past couple of decades have witnessed the global resurgence of medicinal plants in the field of herbal-based health care. Increased consumption of medicinal plants and their derivative products is the major cause of the adulteration issues in herbal industries. As a result, the quality of herbal products is affected by spurious and unauthorized raw materials. Recent development in molecular plant identification using DNA barcodes has become a robust methodology to identify and authenticate the adulterants in herbal samples. Hence, rapid and accurate identification of medicinal plants is the key to success for the herbal industry. Aim of the study: This paper provides a comprehensive review of the application of DNA barcoding and advanced technologies that have emerged over the past ten years related to medicinal plant identification and authentication and the future prospects of this technology. Materials and methods: Information on DNA barcodes was compiled from scientific databases (Google Scholar, Web of Science, SciFinder and PubMed). Additional information was obtained from books, Ph.D. thesis and MSc. dissertations. Results: Working out an appropriate DNA barcode for plants is challenging; the single locus-based DNA barcodes (rbcL, ITS, ITS2, matK, rpoB, rpoC, trnH-psbA) to multi-locus DNA barcodes have become the successful species-level identification among herbal plants. Additionally, multi-loci have become efficient in the authentication of herbal products. Emerging advances in DNA barcoding and related technologies such as next-generation sequencing, high-resolution melting curve analysis, meta barcodes and mini barcodes have paved the way for successful herbal plant/samples identification. Conclusion: DNA barcoding needs to be employed together with other techniques to check and rationally and effectively quality control the herbal drugs. It is suggested that DNA barcoding techniques combined with metabolomics, transcriptomics, and proteomics could authenticate the herbal products. The invention of simple, cost-effective and improved DNA barcoding techniques to identify herbal drugs and their associated products of medicinal value in a fool-proof manner will be the future thrust of Pharmacopoeial monograph development for herbal drugs.